Impact of Student Mobility for Higher Studies on Sustainable Tourism Development - Dimple Bhalla; Praveen Kumar Singh; R.K. Patel (AG Volumes, 2026)
Student mobility is far more than an educational migration; it is a bridge between academia and sustainable tourism. By bringing together diverse cultures, creating steady economic activity, and fostering environmental consciousness, students contribute to tourism models that are inclusive, resilient, and responsible. Harnessing this potential requires coordinated efforts from policymakers, educational institutions, tourism boards, and local communities. In doing so, we can transform the journey of a student into a journey toward a more sustainable and culturally enriched world. Students migrate for higher education, training, competitive exam preparation, and academic events and bring with them a wave of economic and social engagement. This study explores the relationship between student mobility for higher education and the growth of sustainable tourism in India. As an emerging trend, academic mobility contributes to regional economies, promotes cultural exchange, and fosters sustainability through educational tourism. The paper uses secondary data from government and institutional sources, supported by statistical analysis, to assess the positive and negative implications of student mobility on sustainable tourism development. The findings reveal that student migration acts as a catalyst for sustainable tourism, especially in higher education hubs. However, it also highlights challenges like resource stress and infrastructure strain. Policy recommendations are suggested to ensure student-driven mobility supports long-term sustainable tourism.